Gym Management App - Naser Tayeh; Majdy Sabra (My University, 2023)
A gym management app is a software tool supported by web and mobile, designed to help gym owners and trainers Simplify their operations and provide better services to their members The app provides a range of features including member registration and management, Workout scheduling, making custom or advanced plans, and a Nutrition plan, members can purchase supplements, view health tips, and do billing and payment processing. The app is user-friendly and easy to use, allowing gym staff to efficiently manage daily operations and provide better support to members. Additionally, a gym management app can also help with marketing and Advertising by allowing gym owners to send targeted promotions and offers to members based on their interests and preferences. It also provides detailed reporting and analytics to help gym owners track membership growth and revenue. Another benefit of using a gym management app is the ability to provide a better customer experience. Members can easily view workout plans, their membership information, and their progress through the app. They can also receive notifications of new workouts or updates. This helps build a stronger relationship between the gym and its members and fosters a sense of community and engagement. The project aims to address the challenges traditional gym management methods face and improve the efficiency of gym operations. The software will be a valuable tool for gym owners and managers, providing a robust solution for managing their gym and ensuring a positive experience for members. Finally, after searching and gathering information about this idea we got to those points the application isn’t common in the gyms in our country, and a high percentage of new trainees face many problems when start hitting the gym because of the lack of information they have about nutrition plans and the best attitude for targeting mussels and in worst seniors end up with an injury preventing them from doing this sport again so the application will provide all the information needed by providing photographed videos tutorials about all exercises for each muscle and a full meal tutorial provided by the nutrition’s also the application will have a payment method for renewing the monthly fees.